Infectious Endocarditis from Enterococcus faecalis Associated with Tubular Adenoma of the Sigmoid Colon - Emilly Caroline de Freitas Silva; Camila Ronchini Montalvão; Simone Bonafé (Case Reports in Infectious Diseases)
Introduction. Enterococcus faecalis (E. faecalis), a constituent of the gut microbiota, can be associated with both colonic lesions and endocarditis. Since this microorganism is one of the endocarditis etiological agents, there is a need for greater study in regard to the association with endocarditis and colonic lesions. Case Presentation. This is the case description of a 53-year-old man with history of prolapse of the anterior mitral valve leaflet who was diagnosed with endocarditis by E. faecalis and treated with ampicillin and gentamicin. Upon investigation by colonoscopy, he was found to have a tubular adenoma with low grade dysplasia. Conclusion. There are a few descriptions in scientific literature of an association between endocarditis by E. faecalis and colonic lesions. However, further studies with significant correlation between the two pathologies are required, so that proper measures can be implemented in clinical practice.